Komplikasi Endoftalmitis Pasca-operasi Katarak - Elvira; Abdi Sastra Gunanegara (Cermin Dunia Kedokteran, 2023)
The most common intraocular surgery is cataract surgery. Endophthalmitis is a rare complication of intraocular surgery, but very threatening to sight. Intravitreal injection and vitrectomy pars plana are recommended especially in patients with poor visual acuity. Early follow up and appropriate therapies are very important. Late management can change the prognosis of eyesight.